The Masculinity and Its Characteristics Depicted by Dawson Cole as the Main Character in The Best of Me Novel - Mellyuna Ni'mah; Afina Murtiningrum (Journal of Advanced Multidisciplinary Research, 2022)
This study aims to analyzing the characterization of Dawson Cole and to find out the characteristics of masculinity through Dawson Cole’s portrayal. This study focuses on the main character Dawson Cole who has the characteristics of masculinity. It explaining and analyzing the characterization of Dawson Cole using Edward Jones’s characterization theory and Dawson Cole's characteristics of masculinity using Janet Saltzman Chafetz's concept. This study used a descriptive qualitative method. This study finds the masculinity and its characteristics of the main character Dawson Cole. Based on the references used in this study, Dawson's characterization could be found in five ways, they are. characterization through appearance, characterization through dialogue, characterization through external action, characterization through internal action, and characterization through the reaction of other characters. Dawson also has seven masculinity characteristics, they are: physical, a function of the man, sexually aggressive, emotion, intelligence, interpersonal, and other personal.